Healthcare Failure Mode and Effect Analysis (HFMEA) in Reducing Patient Safety Incidents Risk at Hospital: Literature Review - Anggika Yelzi Pratiwi; Masyitoh Basabih (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Patient safety is a priority in hospital services, but patient safety incidents such as adverse events frequently occur in hospitals. Healthcare Failure Mode and Effect Analysis (HFMEA) is one of the hospital’s strategies to reduce patient safety incident risks through risk management. This study aims to describe the use of the HFMEA method in various countries and its role in reducing patient safety incident risks. This study began with searching data using four databases and selecting scientific article sources using the Preferred Reporting Items for Systemic Reviews and Meta-Analysis (PRISMA) method, where 15 articles were found that met the research objectives, inclusion, and exclusion criteria. The result shows that HFMEA has been applied in hospital services and management in various countries. HFMEA reduced the risk of failure and patient safety incidents in the hospital. However, this can be effective if the hospital implements all steps of HFMEA and routine monitoring and evaluation of interventions to prevent the occurrence of patient safety incident risk.